Levantamento de tratamento de dor endodôntica, realizado em pronto atendimento odontológico: necessidade de protocolo - Trizzi, Juliana Quintino [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Endodontic pain affects a large part of the world population, which leads for a seek for urgency treatment. Few reports studied the casuistry and protocol of dental care inserted in the prompt attendance, such as: diagnosis, provisional coronal sealing, intracanal medication, systemic medication and patient with pain complaint. The objective of this study was to carry out a survey of the urgency protocol in both dental care institutions: Prompt Dental Care Services of Araçatuba city (PAO) and the Araçatuba School of Dentistry/Sao Paulo State University Júlio de Mesquita Filho (FOA/UNESP). The medical records of patients who voluntarily sought care in the urgency department, with anamnesis and a description of the performed procedure, were evaluated. Data such as intracanal medication, coronary sealing, systemic medication and patient return with pain complaint were tabulated and statistically evaluated via SigmaPlot 13.0 software, with no association of these variables and the patient return with pain complaint (P> 0.05). However, association (P<0.05) was observed between attendance institution where urgency was carried out and the presence of temporary coronal sealing in cases with abscess, whereas FOA performs the coronal sealing as attendance protocol and PAO doesn’t. There was also an association (P<0.05) between diagnosis, prescription of systemic medication and dental care attendance institution, since PAO performed the largest number of medication prescriptions. It is concluded that, although dental care attendance protocols were similar in cases of pulpitis or necrosis, differing only in abscess, the main objective of urgency treatment was achieved in both treatment protocols, since treated patients were painless for more than 7 days

A dor de caráter endodôntico acomete grande parte da população mundial que procura por tratamento de urgência em pronto atendimento. Poucos trabalhos observam a casuística e o protocolo de atendimento que estão inseridos nos prontos atendimentos como: diagnóstico, presença de selamento coronário provisório, utilização de medicação intracanal, medicação sistêmica e o retorno do paciente com dor. Mediante ao exposto, foi realizado uma pesquisa quantitativa descritiva, retrospectiva e documental, e o levantamento de protocolo de urgência nas seguintes instituições: Serviços de Pronto Atendimento da cidade de Araçatuba (PAO) e na Faculdade de Odontologia da Universidade Estadual Paulista de “Júlio de Mesquita Filho” (FOA/UNESP). Dados como tipo de medicação intracanal, selamento coronário, medicação sistêmica e retorno do paciente com dor foram tabulados e avaliados estatisticamente pelo software SigmaPlot 13.0. O protocolo FOA/PAO foram semelhantes nos diagnósticos de pulpite irreversível e necrose pulpar, não havendo associação (P>0.05). Houve associação (P<0.05) apenas no diagnóstico de abscesso endodôntico, o protocolo do PAO foi prescrever medicação sistêmica, não realizar selamento e não MIC, diferentemente da FOA. Referente a prescrição de medicação sistêmica, houve associação (P<0.05), pois o PAO realiza prescrição em todos os casos: pulpite irreversível, necrose e abscesso, já a FOA apenas em necrose e abscesso. No retorno do paciente com dor, nota-se associação (P<0.05) nos casos de abscesso que receberam MIC adversa e não retornaram com dor. Embora o protocolo FOA/PAO seja diferente para os casos de abscesso o objetivo do tratamento de urgência em ambas instituições foi alcançado, pois removeram a dor do paciente.
Survey of endodontic pain treatment performed In prompt dental care: need for protocol
Keywords: Endodontics; Endodontia; Dor orofacial; Levantamento epidemiológico